2001
DOI: 10.1203/00006450-200101000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Role of Common Gene Variations in the Molecular Pathogenesis of Short-Chain Acyl-CoA Dehydrogenase Deficiency

Abstract: Short-chain acyl-CoA dehydrogenase (SCAD) deficiency is considered a rare inherited mitochondrial fatty acid oxidation disorder. Less than 10 patients have been reported, diagnosed on the basis of ethylmalonic aciduria and low SCAD activity in cultured fibroblast. However, mild ethylmalonic aciduria, a biochemical marker of functional SCAD deficiency in vivo, is a common finding in patients suspected of having metabolic disorders. Based on previous observations, we have proposed that ethylmalonic aciduria in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
120
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 26 publications
2
120
0
4
Order By: Relevance
“…This suggests that there may be other factors, such as environmental or epigenetic, which can trigger the disease symptoms, resulting in the wide range of clinical variability associated with SCAD deficiency [116,117]. Similar to other FAO diseases, SCAD disease can be divided into subgroups based on age of presentation, which can either be in infancy/early childhood or in late adulthood.…”
Section: Disorders Of Fao Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that there may be other factors, such as environmental or epigenetic, which can trigger the disease symptoms, resulting in the wide range of clinical variability associated with SCAD deficiency [116,117]. Similar to other FAO diseases, SCAD disease can be divided into subgroups based on age of presentation, which can either be in infancy/early childhood or in late adulthood.…”
Section: Disorders Of Fao Enzymesmentioning
confidence: 99%
“…In infants, developmental delay, hypotonia and myopathy are common [118]. In addition, ethylmalonic aciduria is a common feature of SCAD deficiency, and as such is a commonly used biomarker of the disease [116].…”
Section: Disorders Of Fao Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Modifier gene group Sixty patients presenting with ethylmalonic aciduria who carried either of two polymorphic SCAD missense variations conferring susceptibility to SCAD deficiency (Corydon et al 2001); although both variant SCAD proteins are functional, they have been shown to cause prolonged association of the variant SCAD proteins with the Hsp60 chaperonin (Pedersen et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Till date, 25 patients have been identified and 50 reported worldwide based upon reduced or absent SCAD activity in vitro [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Genotype-phenotype correlations have been inconsistent [8,18].…”
Section: Discussionmentioning
confidence: 99%